1990
DOI: 10.1016/0304-3959(90)90028-c
|View full text |Cite
|
Sign up to set email alerts
|

Codeine plus paracetamol versus paracetamol in longer-term treatment of chronic pain due to osteoarthritis of the hip. A randomised, double-blind, multi-centre study

Abstract: This randomized, double-blind, multi-centre study was undertaken to evaluate the efficacy and safety of treatment for 4 weeks with codeine plus paracetamol versus paracetamol in relieving chronic pain due to osteoarthritis of the hip. A total of 158 outclinic patients entered the study. Eighty-three patients (mean age 66 years) were treated with codeine 60 mg plus paracetamol 1 g 3 times daily, and 75 patients (mean age 67 years) with paracetamol 1 g 3 times daily. Ibuprofen 400 mg was prescribed as rescue med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
4

Year Published

1995
1995
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(57 citation statements)
references
References 33 publications
2
51
0
4
Order By: Relevance
“…These studies, which have usually assayed codeine or a similar drug in arthritic patients, yielded mixed results and have questionable relevance to long term treatment (81)(82)(83). None has identified a problem with aberrant drug-related behaviours during this brief period of treatment.…”
Section: Pain Res Manage Vol 1 No 1 Spring 1996 19mentioning
confidence: 99%
“…These studies, which have usually assayed codeine or a similar drug in arthritic patients, yielded mixed results and have questionable relevance to long term treatment (81)(82)(83). None has identified a problem with aberrant drug-related behaviours during this brief period of treatment.…”
Section: Pain Res Manage Vol 1 No 1 Spring 1996 19mentioning
confidence: 99%
“…12,35,36,43,44,45,47 This concept was a natural outgrowth of the use of opioids for acute and cancer pain. Subsequent data from multiple case series 17,24,27,42,50,51 and randomized controlled trials 3,5,7,8,13,15,16,19,20,25,26,28,29,30,34,37,39,40,41,48 have supported the use of opioids for this problem; and established medical bodies have developed guidelines supporting opioid use. 4,11,21 In recent years, however, the acceptance of the use of opioids for chronic noncancer pain has been tempered by increasing fears of misuse and safety issues.…”
mentioning
confidence: 93%
“…However, when sensitivity analysis was conducted based on the type of opioids, the strong opioids (oxycodone, morphine) were significantly more effective than other drugs for pain relief (SMD -0.34, 95% CI -0.67 to -0.01). One trial 16 not included in the meta-analysis showed that the addition of codeine to a regimen of acetaminophen was superior to acetaminophen alone at 7 days of follow-up, but not afterward.…”
Section: Effectiveness Of Opioids Compared With Other Drugsmentioning
confidence: 99%